Practicability of Enteritis - prevention in Trekking and Mountaineering at High Altitude by Systematic Hand Disinfection - Hans-Volkhart Ulmer; Julia Risse; Thomas Küpper (University of Applied Sciences in Tarnow, Poland, 2020)
Introduction: The hygienic conditions during trekking or mountaineering at high altitudes are reduced, especially regarding defecation and hand hygiene. An additional problem exists in regions above the snowline, especially in highly frequented regions: snow may be contaminated by faecal microbes, causing diarrhea. Prevention against faecal-oral infections must include not only disinfection of drinking water, but hand disinfection, too, e.g. by a water-free hand gel. The practicability of this measure was tested during a Himalaya expedition on the way to Mt. Everest. Material and methods: 10 participants were instructed to use Stokosept-Gel, an alcohol based skin disinfectant, at least prior to meals, after using a toilet and after handling boot-laces and to note each use (including additional occasions). Results: A very good practicability of using the hand gel, which was absorbed quickly (ca. ¼ min) was reported. 100 ml were sufficient for at least 2 weeks and there were no side effects or problems at the skin. During the mountaineering phase which included a total of 250 person days in the field no diarrhea occurred. Conclusion: We conclude that using such hand gels is - additional to other procedures - a very practical prevention against diarrhea in mountaineering at high altitude.